O software GeoGebra em conceitos básicos da geometria plana: uma metodologia de ensino para o fundamental maior - SAGICA, Felipe Macedo (2022)
The main focus of this study is to address how the use of GeoGebra software can positively impact the learning of basic concepts of plane geometry for the greater fundamental. The general objective is to analyze the main positive impacts of the use of GeoGebra software in basic concepts of plane geometry: a teaching methodology for the higher fundamental. Therefore, the following specific objectives were defined, which will be to present the basic concepts of plane geometry, conceptualize the GeoGebra application, relate basic concepts of plane geometry with the GeoGebra utility and thus promote the construction of the main geometric figures in a didactic way, analyze the main benefits of using the GeoGebra program in the teaching of plane geometry to the higher fundamental. Addressing the theme of this research is justified by the need to show how technology can facilitate the geometric teachinglearning process, and that the importance of the GeoGebra utility in the formation of the student becomes notorious, due to the way in which this computational mechanism can be used. for teaching the basics of plane geometry. The present study consists of a descriptive research, with results treated in a qualitative way, from the collection of data from secondary sources, including a literature review. Books, articles and websites will be used as search sources, along with authors who deal with the importance of reconciling technology and education in the contemporary world. With the collection of information during the research and the analysis of the information, it was possible to conclude that the applications of plane geometry with the GeoGebra software, and said in a positive way by a series of authors who were referenced in this research, because the program provides the user a visual experience of the theoretical concepts seen in class, and this is one of the significant factors for the teaching of geometry.